2015
DOI: 10.1364/ol.40.002882
|View full text |Cite
|
Sign up to set email alerts
|

30  W fluoride glass all-fiber laser at 294  μm

Abstract: We report the demonstration of a 2938 nm erbium-doped fluoride glass fiber laser delivering a record output power of 30.5 W in continuous wave operation. The passively cooled all-fiber laser cavity based on intracore fiber Bragg gratings has an overall laser efficiency of 16% as a function of the launched pump power at 980 nm and a single-mode output beam quality of M2<1.2. This power scaling demonstration of a fiber laser operating near the vibrational resonance of water is likely to have a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
72
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(74 citation statements)
references
References 22 publications
0
72
0
2
Order By: Relevance
“…Recently, 3 µm fiber lasers have shown to exhibit power levels exceeding 30 W CW with peak powers exceeding 0.9 kW. [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 3 µm fiber lasers have shown to exhibit power levels exceeding 30 W CW with peak powers exceeding 0.9 kW. [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant progress has been made in extending the operation of fiber lasers into the mid-infrared, with lasers achieving over 30 W at 3 µm [1]. In a previous publication we demonstrated that dual wavelength pumping (DWP) could significantly increase the efficiency of erbium doped ZBLAN glass fiber lasers that operate on the 3.5 µm transition.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, mid-IR gain fibers that constitute the main element in a mid-IR fiber laser have been developed in recent years. Typical mid-IR gain fibers, such as rare-earth-ion doped fluoride and chalcogenide-based fibers with good mid-IR transparency and high lasing efficiency, can be fabricated [4][5] and utilized in the high-power fiber lasers at around ~3 μm [6][7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…Fiber Bragg gratings (FBGs), characterized by their narrow linewidth and high reflectivity, and above all, convenience of alignment-free operation by avoiding the use of bulky components, are widely used in fiber laser sources to select and tune the lasing wavelength. High-power erbium-doped all-fiber lasers emitting at 2.94 μm and 3.44 μm have been realized by V. Fortin et al using FBGs with the corresponding output spectral linewidth of 0.15 nm and <0.6 nm, respectively [6][7]. However, FBGs are not very effective for wavelength selection and spectral narrowing in large mode area fibers, which can support higher-order transverse modes [13].…”
mentioning
confidence: 99%